Investigation of structural, electronic, mechanical, & optical characteristics of Ra based-cubic hydrides RbRaX3 (X= F and cl) perovskite materials for solar cell applications: First principle study - Muhammad Khuram Shahzad; Muhammad Umair Farooq; Rashid Ali Laghari; Muhammad Aslam Khan; Muhammad Bilal Tahir; Waqar Azeem; Muhammad Mahmood Ali; Vineet Tirth (Heliyon, 2023)
Perovskite materials are considered the gateway of various physical applications to meet the production and consumption of energy and medical fields. Density Functional Theory (DFT) becomes the most important field in the modern era to investigate perovskite materials for various physical properties. DFT nowadays is used to explore the perovskite materials for a lot of applications like photocatalytic, optoelectronic, and photovoltaics. We discussed radium based cubic hydrides RbRaX3 (while X = F & Cl) perovskite material's electrical, optical, elastic, & physical characteristics with the help of DFT-based CASTEP code with PBE exchange-correlation efficient of GGA. The RbRaF3 & RbRaCl3 have three-dimensional nature by means of space group 221 (Pm3 m). According to electronic characteristics, the direct bandgap of RbRaF3 RbRaCl3 are 3.18eV and 2.209eV, respectively. Both compounds are brittle in nature via Poisson's ratio & Pugh's criteria. Thus, our novel RbRaX3 (X = F and Cl) compounds have excellent applications for solar cell and medical areas.